Multidisciplinary investigation on cold seeps with vigorous gas emissions in the Sea of Marmara (MarsiteCruise): Strategy for site detection and sampling and first scientific outcome. (July 2018) - Ruffine, Livio; Ondreas, Hélène; Blanc-Valleron, Marie-Madeleine; Teichert, Barbara M.A.; Scalabrin, Carla; Rinnert, Emmanuel; Birot, Dominique; Croguennec, Claire; Ponzevera, Emmanuel; Pierre, Catherine; Donval, Jean-Pierre; Alix, Anne-Sophie; et al.
Abstract: MarsiteCruise was undertaken in October/November 2014 in the Sea of Marmara to gain detailed insight into the fate of fluids migrating within the sedimentary column and partially released into the water column. The overall objective of the project was to achieve a more global understanding of cold-seep dynamics in the context of a major active strike-slip fault. Five remotely operated vehicle (ROV) dives were performed at selected areas along the North Anatolian Fault and inherited faults. To efficiently detect, select and sample the gas seeps, we applied an original procedure. It combines sequentially (1) the acquisition of ship-borne multibeam acoustic data from the water column prior to each dive to detect gas emission sites and to design the tracks of the ROV dives, (2) in situ and real-time Raman spectroscopy analysis of the gas stream, and (3) onboard determination of molecular and isotopic compositions of the collected gas bubbles. The in situ Raman spectroscopy was used as a decision-making tool to evaluate the need for continuing with the sampling of gases from the discovered seep, or to move to another one. Push cores were gathered to study buried carbonates and pore waters at the surficial sediment, while CTD-Rosette allowed collecting samples to measure dissolved-methane concentration within the water column followed by a comparison with measurements from samples collected with the submersible Nautile during the Marnaut cruise in 2007. Overall, the visited sites were characterized by a wide diversity of seeps. CO2 - and oil-rich seeps were found at the westernmost part of the sea in the Tekirdag Basin, while amphipods, anemones and coral populated the sites visited at the easternmost part in the Cinarcik Basin. Methane-derived authigenic carbonates and bacterial mats were widespread on the seafloor at all sites with variable size and distributions. The measured methane concentrations in the water column were up to 377 μmol, and the dissolved pore-water profiles indicated the occurrence of sulfate depleting processes accompanied with carbonate precipitation. The pore-water profiles display evidence of biogeochemical transformations leading to the fast depletion of seawater sulfate within the first 25-cm depth of the sediment. These results show that the North Anatolian Fault and inherited faults are important migration paths for fluids for which a significant part is discharged into the water column, contributing to the increase of methane concentration at the bottom seawater and favoring the development of specific ecosystems.